Differential Gene Expression from Two Transcriptional Units in the cag Pathogenicity Island of Helicobacter pylori - Joyce, Elizabeth A. (American Society for Microbiology, 2001)
Infection with Helicobacter pylori strains containing the cag Pathogenicity Island (cag PAI) is strongly correlated with the development of severe gastric disease, including gastric and duodenal ulceration, mucosa-associated lymphoid tissue lymphoma, and gastric carcinoma. Although in vitro studies have demonstrated that the expression of genes within the cag PAI leads to the activation of a strong host inflammatory response, the functions of most cag gene products and how they work in concert to promote an immunological response are unknown. We developed a transcriptional reporter that utilizes urease activity and in which nine putative regulatory sequences from the cag PAI were fused to the H. pylori ureB gene. These fusions were introduced in single copies onto the H. pylori chromosome without disruption of the cag PAI. Our analysis indicated that while each regulatory region confers a reproducible amount of promoter activity under laboratory conditions, they differ widely in levels of expression. Transcription initiating upstream of cag15 and upstream of cag21 is induced when the respective fusion strains are cocultured with an epithelial cell monolayer. Results of mouse colonization experiments with an H. pylori strain carrying the cag15-ureB fusion suggested that this putative regulatory region appears to be induced in vivo, demonstrating the importance of the urease reporter as a significant development toward identifying in vivo-induced gene expression in H. pylori.